Depression, anxiety, and stress among diabetic patients in Ghana: a health facility–based mixed-method cross-sectional study at Volta Regional Hospital - Emmanuel Abu Bonsra; Felix Mbiba; Emmanuel Adjei Kyeremeh; Gideon Amankwah Kyere; Mark Kwame Ananga (BMC Public Health)
Abstract Background Despite global health initiatives, such as the Sustainable Development Goals (SDGs), mental health challenges remain significant public health concerns worldwide especially those with chronic non-communicable diseases like diabetes. Individuals with diabetes frequently contend with depression, anxiety, and stress, which complicate the management of their condition and adherence to treatment, ultimately diminishing their quality of life. This study aimed to assess depression, anxiety, and stress among diabetic patients in the Volta Regional Hospital, Ghana. Methods A health facility-based mixed-methods cross-sectional study was conducted at the volta regional hospital among 422 diabetic patients selected through simple random sampling and purposively sampled healthcare personnel. Depression, anxiety, and stress were assessed using the DASS-21 scale. Quantitative data were collected via Kobocollect and analysed using descriptive statistics and binary logistic regression with Stata 17.0. Qualitative data from key informant interviews were transcribed and thematically analysed using ATLAS.ti. Results Out of the total respondents (422), 205 (48.6%) exhibited symptoms of depression, 160 (37.9%) reported symptoms of anxiety, and 180 (42.6%) experienced elevated stress levels. Logistic regression analysis revealed that participants who had lived with diabetes for more than 24 months were 86% less likely to exhibit symptoms of depression (OR = 0.14, 95% CI: 0.05–0.43, p < 0.01), 77% less likely to be anxious (AOR = 0.23, 95% CI: 0.08–0.70, p = 0.009), and 92% less likely to be stressed (AOR = 0.08, 95% CI: 0.02–0.30, p < 0.001) compared to those who had been diagnosed for less than six months. Qualitative results show that systemic factors such as resource constraints, insufficient staff, limited mental health integration, patient self-management challenges, and human resources contribute to poor mental health outcomes. Conclusion This research reveals substantial levels of depression, anxiety, and stress among diabetic patients. It indicates that a longer duration of diabetes may be linked to lower levels of depression and stress, likely due to better coping strategies. These results emphasize the need for Ghana Health Service to incorporate mental health services into diabetes management and consider socio-demographic and cultural differences. Addressing these factors is crucial for advancing toward the SDG 3.4 goal of enhancing mental health and well-being.